Hubungan Pengetahuan Dan Tingkat Konsumsi Serat Dengan Status Gizi Remaja Putri Di Smk Batik 2 Surakarta - Baiti, Alfi Nur, Dr. Mutalazimah, SKM, M.Kes, Endang Nur W, S.St., M.Si.Med (2015)
Introduction: Nutritional status is a state that is determined by the degree of physical needs for energy and nutrients derived from food intake physical impact can be measured. Objective: The purpose of this researchwas to know correlation between knowledge and fiber intake with the nutritional status among female students at Vocational High School of Batik 2 Surakarta. Research Method: This research was an observational study using cross-sectional design. Knowledge with questionnaire, fiber intake were collected using recall 24 hours form for 3 days. As for the nutritional status obtained by measurements anthropometric. There were 67 respondents participated taken using simple random sampling method. The correlation test used Pearson test Results: The result showed that adolescent knowledge fiber 13.4%, and good 19.4%. As for the consumption of fiber girls SMK Batik 2 Surakarta included in the poor category ≤ 25 g / day. The nutritional status of young women who are underweight of 4.5% and 9% were obese. The research also showed no correlation between between knowledge and nutritional status with p-value p=0.109. Also there was no correlation between fiber intake and nutritional status with p-value p=0.255. Conclusion: There were no relationship between knowledge and fiber intake and nutritional status of the nutritional status among female students at Vocational High School of Batik 2 Surakarta.